Possible Problems with the Use of Regional Ratings - A. K. Zhikhareva (North-West institute of management of the Russian Presidential Academy of National Economy and Public Administration, 2019)
The article is devoted to the problems of applying regional ratings. It is shown that at each stage of ratings’ calculation there are several problems and assumptions that impose restrictions on their use in statistical and econometric analysis. At the same time, in the absence of real alternatives to integral indices, on the basis of which rating scores are built, it is necessary to continue working on their improvement in order to use them as analysis tools and strategic management  decision-making factors.